How sport and exercise medicine can emerge stronger from a global crisis - Pitsiladis, Y.; Webborn, N.; Guppy, F.; Wang, G.; Smeeton, N. (BASEM, 2020)
It is a great honour to have been given the opportunity and responsibility to edit this special edition with my good friend and colleague Professor Nick Webborn, with the most relevant theme - "How Sport and Exercise Medicine Can Emerge Stronger from a Global Crisis". Nick and I became colleagues in late 2013 at the University of Brighton`s current branding of the historic Chelsea College which was founded in 1898. Within a year, our research facilities were awarded the status of International Federation of Sports Medicine (FIMS) Reference Collaborating Centre of Sports Medicine for Anti-Doping Research with current affiliation to the FIMS Collaborating Centre of Sports Medicine (FIMS CCSM) at "Foro Italico" University of Rome - one of 26 FIMS CCSM worldwide (www.fims.org/about/ccsm/collaborating-centers-of-sports-medicine-worldwide/). Nick and I have experienced an exciting roller coaster ride to systematically strengthen research with a mission to establish Eastbourne as a centre of excellence in sport and exercise medicine within a decade. This ambitious goal is on track as evidenced by the range of high quality research in sport and exercise medicine being conducted and celebrated in this special edition. The COVID-19 pandemic has provided a real opportunity for reflection on integrity challenges facing elite sport and sports medicine. The imposed lockdown in response to this global crisis has resulted in most sporting events being postponed or cancelled including the 2020 Olympic Games. While this pandemic has overwhelmed an already fragile world sport, it provides an unprecedented opportunity for stakeholders in sport to learn vital lessons from COVID-19, to delve into unresolved integrity issues and develop creative and long-lasting solutions. This special edition focuses on three main issues affecting the integrity of elite sport: doping, technological fairness/opportunities and the fair integration of intersex and transgender athletes in elite sport (see Figure 1). The word most associated with COVID-19 is "unprecedented" but you are reminded that very deadly pandemics have struck numerous times over the past 2000 years. What is unprecedented but positive during this pandemic, is that science and medicine are moving at quantum speed. There are many large international collaborations aimed at understanding the virus and developing effective and safe vaccines and treatments. It is unprecedented also to see so many papers from scientists around the world collaborating in all areas of science, working together on this common cause. Within countries and between countries, exciting collaborations between academic and commercial institutions and many other entities, all coming together to solve the incredible challenges that come with Covid-19. The main difference from previous pandemics are the readily available technologies that enable us to work from home, teach students on-line and remotely treat patients in hospitals/care homes. Genetic sequencing of the virus and human genomes are creating solutions to help us emerge from this pandemic quicker. It is essential that sport and exercise medicine embraces new technologies such as genetic sequencing, deep/machine learning, artificial intelligence, wearable technologies and matches the unprecedented levels of collaboration recently seen in response to the pandemic in order for sport and exercise medicine to emerge stronger from this global crisis. Our special edition is hoped to serve as an exemplar of our united efforts to lead our researchers and students while dealing with some of the biggest challenges facing modern day sport (medicine).